The integrating factor method for solving the steady heat transfer problems in fractal media - Chen Shan-Xiong (Thermal Science, 2016)
In this paper, we propose the integrating factor method via local fractional derivative for the first time. We use the proposed method to handle the steady heat-transfer equations in fractal media with the constant coefficients. Finally, we discuss the non-differentiable behaviors of fractal heat-transfer problems.